Pengaruh Safety Culture Terhadap Safety Behavior Melalui Safety Awareness Pada Objek Wisata Boekit Tawap Sumenep - Tiawati, Tiawati; Faidal, Faidal (Jurnal Ilmiah Pariwisata, 2024)
This research aims to examine the influence of safety culture on safety behavior through safety awareness at the Bukit Tawap tourist attraction, Saronggi District, Sumenep, East Java. The background to this research is based on the importance of a good safety culture in reducing work accidents and increasing awareness of dangers in the workplace. This research uses quantitative methods with a path analysis design. The sample used was 88 respondents consisting of permanent employees, investors and tourism managers, using a proportional stratified random sampling technique. Data was collected through a questionnaire using a 1-5 Likert scale. The research results show that safety culture has a positive and significant effect on safety behavior and safety awareness, and fully mediates the influence of safety awareness on safety behavior. These findings suggest that a good safety culture can increase safety awareness and encourage better safety behavior. This research suggests that tourist attraction managers strengthen safety training programs and effective communication to create a safer work environment, as well as increase safety awareness among employees and visitors. Keywords: safety culture, safety behavior, safety awareness